In vitro assessment of drug delivery through an endotracheal tube using a dry powder inhaler delivery system. - Everard, M. L. (1996)
BACKGROUND: Jet nubulisers and metered dose inhalers are widely used to deliver aerosolised drugs to the lungs of intubated patients in adult intensive care units. Drug delivery using these systems has been shown to be inefficient and both forms of delivery have the potential to induce paradoxical bronchoconstriction in patients with reactive airways disease. METHODS: Experiments were carried out to determine whether it was possible to deliver drug from a dry powder delivery system through an endotracheal tube. A 200 micrograms budesonide Turbohaler was enclosed in a chamber which allowed it to be inserted into a ventilator circuit. Experiments were performed with a multistage liquid impinger in which drug was drawn through the Turbohaler and endotracheal tube at 60 l/min providing an index of the maximum drug delivery achievable via this route. A second series of experiments was performed in which the Turbohaler was placed in a ventilator circuit using a Servo 900C volume cycled ventilator. Drug delivered from the Turbohaler during the inspiratory phase was collected on a filter placed between the end of a 9 mm endotracheal tube and a model lung. A tidal volume of 500 ml and inspiratory time of 0.5 seconds was used. Budesonide was assayed using an ultraviolet spectrophotometric assay. RESULTS: Thirty percent of the nominal dose passed through the endotracheal tube and was collected in the multistage liquid impinger. Mean drug delivery to the filter in the ventilator circuit was 20%. CONCLUSIONS: This in vitro study indicates that drugs from dry powder inhalers (in this case the Turbohaler) can be satisfactorily delivered through endotracheal tubes and that clinical evaluation of this technique is now indicated.